An Assessment of Boko Haram Crisis and the Socio-Political Development of Borno State, Nigeria - Galadima , Zanna (Journal of Public Policy and Administration, 2023)
Purpose: This research work attempt to examine the Boko Haram crisis in Borno State and how it undermines socio-political development, with Maiduguri being our case study. The work has five chapters, each chapter structured in analysing the Boko Haram crisis in Nigeria and how it affects the socio-political development of Borno State. Methodology: the research developed twelve questions, these questions were administered in form of questionnaires to 400 people who were selected as a sample of the population primary and secondary data were used as a source of data while tables and percentages were used in organizing and presenting the data collected. Findings: The data analysis revealed that Boko Haram crisis has created so many backwardness, hatred, national disintegration and lack of unity in Nigeria. Unique Contribution to Theory, Practice and Policy: The researcher therefore recommended that for Boko Haram crisis to be prevented, the government should take adequate measures to shut down any training terrorist camps operated by the Boko Haram sect. Then, the nation will start experiencing peace, oneness, security, national unity, development and progress for the betterment of all Nigerians.